Histoire à travers identité et mémoire dans Ce que le jour doit à la nuit de Yasmina Khadra - Benkamla, Amina, author; Vogl, Mary, advisor; Hirchi, Mohammed, committee member; Duffy, Andrea, committee member (Colorado State University. Libraries, 2018)
The purpose of this research is to demonstrate how history can be represented in literary fiction by providing the example of the Francophone Algerian novel What the Day Owes the Night. Published in 2008, Yasmina Khadra's novel inscribes itself in the literary history of the novelists who wrote on the troubled past of France and Algeria. Fictional literature has been a way to lift the veil on France's colonial past in Algeria and has given a voice to those whose lives have been impacted by the war. By combining historical research and literary analysis, I have been able to identify two prominent concepts in Khadra's work: identity and memory. The question of identity is omnipresent and the different characters represent the different populations involved during the conflict. Identity is strongly linked to the characters' memory of the war and French and Algerian collective memories reflect in the characters themselves.